Bio-based foaming material and preparation method thereof

By introducing materials such as spiropyran ultraviolet absorber, ethylene-vinyl acetate copolymer, modified nanosilica and phytic acid into the bio-based foaming material, bio-based with excellent antibacterial, wear-resistant and flame retardant properties can be produced. Foaming materials solve the problems of insufficient comfort and durability of traditional shoe materials and meet the needs of functional shoe materials.

CN119391098AActive Publication Date: 2025-02-07ALPHA (GUANGDONG) HIGH-TECH MATERIALS CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411510901.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Traditional shoe materials have problems such as bulky, breathable, easy to wear, and poor comfort, which is difficult to meet people's demand for functional shoe materials, especially in sports or humid environments that are prone to breeding microorganisms that affect health.

Method used

Using bio-based foaming materials, the materials are mixed granulated and supercritical foamed by mixing materials such as spiropyran ultraviolet absorber, ethylene-vinyl acetate copolymer, modified nanosilica, phytic acid, etc., which gives the material excellent Antibacterial, wear-resistant and flame retardant properties.

Benefits of technology

It improves the antibacterial, wear-resistant and flame-retardant properties of bio-based foaming materials, enhances wear comfort, meets the market's demand for functional shoe materials, and reduces microbial growth in humid environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105430100000111
    Figure BDA0005105430100000111
  • Figure BDA0005105430100000121
    Figure BDA0005105430100000121
Patent Text Reader

Abstract

The invention discloses a bio-based foaming material and a preparation method thereof, and relates to the technical field of foaming materials. When the bio-based foaming material is prepared, (1, 3, 3-trimethyl-2-methylene-2, 3-dihydro-1H-indole-6-yl)-methanol and 3-allyl salicylaldehyde are subjected to a reaction, and a spiropyran ultraviolet absorbent is prepared; the preparation method comprises the following steps: reacting a spiropyrane ultraviolet absorbent with an ethylene-vinyl acetate copolymer to prepare a modified ethylene-vinyl acetate copolymer; the preparation method comprises the following steps: carrying out polymerization growth on pre-modified nano silicon dioxide by using 1, 3-diaminoguanidine hydrochloride and 2, 4-diamino-6-[3-(trifluoromethyl) phenyl]-1, 3, 5-triazine to prepare modified nano silicon dioxide; the modified ethylene-vinyl acetate copolymer, the styrene-butadiene block copolymer, the modified nano silicon dioxide and phytic acid are mixed, granulated and subjected to supercritical foaming, and the bio-based foaming material is prepared. The bio-based foaming material prepared by the invention has excellent anti-aging, flame-retardant, antibacterial and wear-resistant properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, in particular to a bio-based foaming material and a preparation method thereof. Background Art

[0002] In modern society, people's pursuit of a better life has led to a great change in the public's concept of wearing shoes, from protection and heat preservation in the last century to the pursuit of comfort, lightness, beauty, shock absorption and other functions. Traditional shoe materials are generally animal leather, natural rubber, polyvinyl chloride and other polymer materials. The shoes made have problems such as bulky, airtight, easy to wear, and poor comfort, which makes it difficult to meet people's demand for functional shoe materials; not only that, when exercising a lot or working and living in a humid and hot environment, the sweat secreted by the human foot will provide a favorable environment for the growth of microorganisms and affect people's health. This series of problems has prompted shoemaking companies to actively seek innovation and creation to develop new shoe materials that meet market demand.

[0003] Based on the existing technical problems, the present application proposes a bio-based foaming material and a preparation method thereof, and prepares a bio-based foaming material with excellent antibacterial and wear-resistant properties as a new type of shoe material, thereby improving wearing comfort and meeting the market demand for functional shoe materials. Summary of the invention

[0004] The purpose of the present invention is to provide a bio-based foaming material and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A bio-based foaming material, wherein the bio-based foaming material is prepared by reacting a spiropyran ultraviolet absorber and an ethylene-vinyl acetate copolymer to obtain a modified ethylene-vinyl acetate copolymer; polymerizing and growing 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine on pre-modified nano-silica to obtain modified nano-silica; and mixing and granulating the modified ethylene-vinyl acetate copolymer, a styrene-butadiene block copolymer, the modified nano-silica and phytic acid, and performing supercritical foaming to obtain the bio-based foaming material;

[0007] The spiropyran ultraviolet absorber is prepared by reacting (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde;

[0008] The pre-modified nano silicon dioxide is prepared by reacting nano silicon dioxide and 3-aminopropyltriethoxysilane.

[0009] A method for preparing a bio-based foaming material, the method for preparing a bio-based foaming material comprising the following preparation steps:

[0010] (1) mixing spiropyran ultraviolet absorber, diisopropyl peroxide and acetone in a mass ratio of 1:(0.1-0.12):(3-4), stirring at 10-30°C and 300-500 r / min for 3-5 min, adding ethylene-vinyl acetate copolymer in an amount of 45-55 times the mass of the spiropyran ultraviolet absorber, continuing stirring for 10-12 min, standing for 11-13 h, placing in a plasticizer for melting and plasticizing, setting the plasticizing temperature to 170-180°C, the screw speed to 40-50 r / min, the plasticizing time to 10-12 min, and drying at 50-60°C under vacuum conditions for 3-4 h to obtain a modified ethylene-vinyl acetate copolymer;

[0011] (2) adding pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride, and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine in a mass ratio of 1:(0.4-0.6):(0.3-0.5) into a reaction kettle, stirring at 160-180° C. and 400-600 r / min for 3-4 h, cooling to 70-80° C., stirring for 1-2 h, washing with anhydrous ethanol and deionized water for 3-5 times each, and drying at 50-60° C. for 7-8 h under vacuum conditions to obtain modified nano-silica;

[0012] (3) Weigh 30-40 parts by mass of modified ethylene-vinyl acetate copolymer, 10-20 parts by mass of styrene-butadiene block copolymer, 1-2 parts by mass of modified nano-silicon dioxide, and 1-1.5 parts by mass of zinc stearate, mix them evenly, place them in a twin-screw extruder for mixing and granulation, and prepare a mixed masterbatch; mix the mixed masterbatch, phytic acid, and di-tert-butyl peroxide isopropyl benzene in a mass ratio of 1:(0.06-0.08):(0.03-0.04), place them in an internal mixer, and heat at 150-1 The mixture was mixed at 60°C and 300-500r / min for 10-20min, then placed in an open mill, thinned 6-8 times at 150-160°C, pressed into a plate on a flat vulcanizer, and then placed in a high-pressure foaming kettle, using nitrogen as a foaming agent for supercritical foaming, setting the pressure of the high-pressure foaming kettle to 24-28MPa and the temperature to 175-185°C, releasing the pressure after 1-2h, and the pressure release time to 15-25s. The mixture was cooled to room temperature to obtain a bio-based foaming material.

[0013] As an optimization, the preparation method of the spiropyran ultraviolet absorber in step (1) is: (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde are added in a molar ratio of 1:1 to methanol with a mass of 14 to 16 times that of 3-allyl salicylaldehyde, and the mixture is stirred and refluxed at 65 to 75°C and 300 to 500 r / min for 2 to 3 hours under a nitrogen atmosphere, and dried at 50 to 60°C for 7 to 9 hours under vacuum conditions to obtain the spiropyran ultraviolet absorber.

[0014] As an optimization, the model of the ethylene-vinyl acetate copolymer in step (1) is Y2045 18-3.

[0015] As an optimization, the preparation method of the pre-modified nano-silica in step (2) is: nano-silica and anhydrous ethanol are mixed evenly in a mass ratio of 1: (20-30), silane hydrolyzate is added in an amount of 8-10 times the mass of the nano-silica, the reaction is stirred at 50-60° C. and 300-500 r / min for 2-3 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 70-80° C. under vacuum conditions for 8-10 hours to obtain pre-modified nano-silica.

[0016] As an optimization, the preparation method of the silane hydrolyzate is: 3-aminopropyltriethoxysilane and anhydrous ethanol are mixed evenly in a mass ratio of 1:(40-50), the pH is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare a silane hydrolyzate.

[0017] As an optimization, the model of the styrene-butadiene block copolymer in step (3) is: HJ15A.

[0018] As an optimization, the process parameters of the twin-screw extruder in step (3) are as follows: the temperature of the twin-screw extruder is set to 170-180° C., and the screw speed is set to 90-100 r / min.

[0019] As an optimization, the process parameters of the plate vulcanizer in step (3) are as follows: the temperature of the plate vulcanizer is set to 140-150° C., the pressure is set to 14-16 MPa, and the time is set to 8-10 min.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] When preparing the bio-based foaming material, the present invention comprises the following steps: (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde are reacted to obtain a spiropyran ultraviolet absorber; the spiropyran ultraviolet absorber and ethylene-vinyl acetate copolymer are reacted to obtain a modified ethylene-vinyl acetate copolymer; nano silicon dioxide and 3-aminopropyltriethoxysilane are reacted to obtain pre-modified nano silicon dioxide; 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are polymerized and grown on the pre-modified nano silicon dioxide to obtain modified nano silicon dioxide; and modified ethylene-vinyl acetate copolymer, styrene-butadiene block copolymer, modified nano silicon dioxide and phytic acid are mixed and granulated, and supercritical foaming is performed to obtain the bio-based foaming material.

[0022] Firstly, (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde are reacted to obtain a spiropyran ultraviolet absorber, and a carbon-carbon double bond and a hydroxymethyl group are introduced into the spiropyran ultraviolet absorber; the spiropyran ultraviolet absorber has two aromatic rings connected by an SP3 hybridized spiro carbon atom, which are orthogonal to each other, do not produce molecular structural conjugation, and form a closed ring body. After being excited by ultraviolet light, the spiro oxygen bond in the molecule undergoes heterolysis and the electronic configuration undergoes isomerization or rearrangement, and becomes a coplanar open ring body of two ring systems, and the whole molecule forms a large conjugated plane, and the open ring body is irradiated with visible light. Under irradiation or heating, it can be re-closed to form a closed-loop body, thus giving the bio-based foaming material excellent anti-ultraviolet aging properties; the carbon-carbon double bond in the spiropyran UV absorber is melt-grafted onto the side chain of ethylene-vinyl acetate copolymer to obtain a modified ethylene-vinyl acetate copolymer, and hydroxymethyl is introduced into the side chain of the modified ethylene-vinyl acetate copolymer. The hydroxymethyl can be dehydrated with the phosphate group on the phytic acid under high temperature and high pressure to form a cross-linked network, inhibiting the relative slip of the molecular chains, making the final pore structure stable, and at the same time improving the mechanical properties of the bio-based foaming material. The molecular chains are not easily torn by external shear forces, thereby enhancing the wear resistance.

[0023] Secondly, nano-silica and 3-aminopropyltriethoxysilane are reacted to obtain pre-modified nano-silica, amino groups are introduced into the pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are polymerized and grown on the pre-modified nano-silica to obtain modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are deammonia-free and thermally condensed at high temperature, and guanidine salt structure, triazine structure, fluorine atoms and amino groups are introduced into the modified nano-silica. The introduction of guanidine salt structure can give the bio-based foaming material excellent antibacterial properties, and the triazine structure can generate non-flammable nitrogen-containing gas, absorb heat, dilute oxygen concentration, and improve the flame retardant properties of the bio-based foaming material. The atoms have low reactivity and are hydrophobic and oleophobic, which can enhance the anti-fouling and corrosion resistance of bio-based foaming materials. The amino groups on the modified nano-silica can also be dehydrated with the phosphate groups on the phytic acid under high temperature and high pressure to form a cross-linked network, inhibiting the relative slip of the molecular chains, making the final pore structure stable, and at the same time improving the mechanical properties of the bio-based foaming materials. The molecular chains are not easily torn by external shear forces, thereby enhancing the wear resistance. Nano-silica has a high specific surface area and excellent mechanical properties, which can improve the strength and hardness of the matrix resin. The nano-silica is modified to increase the compatibility of the nano-silica with the matrix resin, reduce the agglomeration of the nano-silica, and make the nano-silica evenly dispersed in the matrix resin, so as to give full play to the reinforcing effect of the nano-silica and further enhance the wear resistance of the bio-based foaming materials.

[0024] Finally, the modified ethylene-vinyl acetate copolymer, styrene-butadiene block copolymer, modified nano-silica and phytic acid are mixed and granulated, and supercritical foaming is used to obtain a bio-based foaming material. Phytic acid is an organophosphorus compound extracted from plant seeds, which contains a large amount of phosphorus and phosphate groups. The introduction of phytic acid can not only further improve the flame retardant properties of the bio-based foaming material, but the phosphate groups in phytic acid can also dehydrate with the hydroxymethyl groups on the modified ethylene-vinyl acetate copolymer and the amino groups on the modified nano-silica under high temperature and high pressure to form a cross-linked network, inhibiting the relative slip of the molecular chains, making the final pore structure stable, and at the same time improving the mechanical properties of the bio-based foaming material, making the molecular chains not easily torn by external shear forces, thereby enhancing the wear resistance. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] A method for preparing a bio-based foaming material, the method for preparing a bio-based foaming material comprising the following preparation steps:

[0028] (1) (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde were added in a molar ratio of 1:1 to methanol (14 times the mass of 3-allyl salicylaldehyde), and the mixture was stirred and refluxed at 65°C and 300 r / min for 3 h under a nitrogen atmosphere, and dried at 50°C for 9 h under vacuum conditions to obtain a spiropyran ultraviolet absorber; the spiropyran ultraviolet absorber, diisopropyl peroxide, and acetone were added in a molar ratio of 1:1. The mixture was mixed evenly at a mass ratio of 1:0.1:3, stirred at 10°C and 300 r / min for 5 min, ethylene-vinyl acetate copolymer with a mass of 45 times that of the spiropyran UV absorber was added, stirred for 12 min, allowed to stand for 13 h, placed in a plasticizer for melt plasticization, the plasticization temperature was set to 170°C, the screw speed was 40 r / min, the plasticization time was 12 min, and dried at 50°C under vacuum conditions for 4 h to obtain a modified ethylene-vinyl acetate copolymer;

[0029] (2) 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:40, the pH was adjusted to 4 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 10°C and 300 r / min for 60 min to prepare a silane hydrolyzate; nano-silicon dioxide and anhydrous ethanol were mixed at a mass ratio of 1:20, silane hydrolyzate with a mass of 8 times that of nano-silicon dioxide was added, and the mixture was stirred at 50°C and 300 r / min for 3 h, filtered, washed with anhydrous ethanol for 3 times, and heated at 70°C under vacuum. Dry for 10 hours to obtain pre-modified nano-silica; add pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride, and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine into a reactor at a mass ratio of 1:0.4:0.3, stir and react at 160°C and 400r / min for 4 hours, cool to 70°C, continue to stir and react for 2 hours, wash with anhydrous ethanol and deionized water 3 times each, and dry at 50°C for 8 hours under vacuum conditions to obtain modified nano-silica;

[0030] (3) Weigh 30 parts by mass of modified ethylene-vinyl acetate copolymer, 10 parts by mass of styrene-butadiene block copolymer, 1 part by mass of modified nano-silicon dioxide, and 1 part by mass of zinc stearate, mix them evenly, place them in a twin-screw extruder for mixing and granulation, set the temperature of the twin-screw extruder to 170° C., and the screw speed to 90 r / min to obtain a mixed masterbatch; mix the mixed masterbatch, phytic acid, and di-tert-butyl peroxide isopropylbenzene in a mass ratio of 1:0.06:0.03, place them in an internal mixer, and heat at 150° C. The mixture was mixed for 20 minutes under stirring conditions at 300 r / min, and then placed in an open mixing mill, thinned 8 times at 150°C, and pressed into a plate on a flat vulcanizer. The temperature of the flat vulcanizer was set to 140°C, the pressure was set to 14 MPa, and the time was 10 minutes. The mixture was then placed in a high-pressure foaming kettle, and nitrogen was used as a foaming agent for supercritical foaming. The pressure of the high-pressure foaming kettle was set to 24 MPa, and the temperature was set to 175°C. The pressure was released after 2 hours, and the pressure release time was 15 seconds. The mixture was cooled to room temperature to obtain a bio-based foaming material.

[0031] Example 2

[0032] A method for preparing a bio-based foaming material, the method for preparing a bio-based foaming material comprising the following preparation steps:

[0033] (1) (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde were added in a molar ratio of 1:1 to methanol (15 times the mass of 3-allyl salicylaldehyde), stirred and refluxed at 70°C and 400 r / min for 2.5 h under a nitrogen atmosphere, and dried at 55°C for 8 h under vacuum conditions to obtain a spiropyran ultraviolet absorber; the spiropyran ultraviolet absorber, diisopropyl peroxide, and acetone were added in a molar ratio of 1:1. The mixture was mixed in a ratio of 1:0.11:3.5, stirred at 20°C and 400r / min for 4min, ethylene-vinyl acetate copolymer with a mass of 50 times that of spiropyran UV absorber was added, stirred for 11min, allowed to stand for 12h, placed in a plasticizer for melting and plasticization, the plasticizing temperature was set to 175°C, the screw speed was 45r / min, the plasticizing time was 11min, and dried at 55°C under vacuum for 3.5h to obtain a modified ethylene-vinyl acetate copolymer;

[0034] (2) 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:45, the pH was adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; nano-silicon dioxide and anhydrous ethanol were mixed at a mass ratio of 1:25, 9 times the mass of nano-silicon dioxide was added to the silane hydrolyzate, and the mixture was stirred at 55°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol 4 times, and dried at 75°C under vacuum conditions. 9h to obtain pre-modified nano-silica; add pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride, and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine into a reactor at a mass ratio of 1:0.5:0.4, stir and react at 170°C and 500r / min for 3.5h, cool to 75°C, continue to stir and react for 1.5h, wash with anhydrous ethanol and deionized water 4 times each, and dry at 55°C under vacuum conditions for 7.5h to obtain modified nano-silica;

[0035] (3) 35 parts of modified ethylene-vinyl acetate copolymer, 15 parts of styrene-butadiene block copolymer, 1.5 parts of modified nano-silica and 1.25 parts of zinc stearate were weighed and mixed uniformly, and then placed in a twin-screw extruder for mixing and granulation. The temperature of the twin-screw extruder was set to 175° C. and the screw speed was set to 95 r / min to obtain a mixed masterbatch; the mixed masterbatch, phytic acid and di-tert-butyl peroxide isopropyl benzene were mixed in a mass ratio of 1:0.07:0.035, placed in an internal mixer, and heated at 155 ℃, knead for 15 minutes under stirring conditions of 400r / min, then place it in an open mill, thin pass 7 times at 155℃, place it on a flat vulcanizer to press into a plate, set the temperature of the flat vulcanizer to 145℃, the pressure to 15MPa, the time to 9min, then place it in a high-pressure foaming kettle, use nitrogen as a foaming agent for supercritical foaming, set the pressure of the high-pressure foaming kettle to 26MPa, the temperature to 180℃, release the pressure after 1.5h, the pressure release time is 20s, cool to room temperature, and obtain a bio-based foaming material.

[0036] Example 3

[0037] A method for preparing a bio-based foaming material, the method for preparing a bio-based foaming material comprising the following preparation steps:

[0038] (1) (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde were added in a molar ratio of 1:1 to methanol (16 times the mass of 3-allyl salicylaldehyde), and the mixture was stirred and refluxed at 75°C and 500 r / min for 2 h under a nitrogen atmosphere, and dried at 60°C for 7 h under vacuum conditions to obtain a spiropyran ultraviolet absorber; the spiropyran ultraviolet absorber, diisopropyl peroxide, and acetone were added in a molar ratio of 1:1. The mixture was mixed evenly at a mass ratio of 1:0.12:4, stirred at 30°C and 500r / min for 3min, ethylene-vinyl acetate copolymer with a mass of 55 times that of the spiropyran UV absorber was added, stirred for 10min, allowed to stand for 11h, placed in a plasticizer for melting and plasticization, the plasticizing temperature was set to 180°C, the screw speed was 50r / min, the plasticizing time was 10min, and dried at 60°C under vacuum conditions for 3h to obtain a modified ethylene-vinyl acetate copolymer;

[0039] (2) 3-aminopropyltriethoxysilane and anhydrous ethanol were mixed at a mass ratio of 1:50, the pH was adjusted to 6 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 30°C and 500 r / min for 50 min to prepare a silane hydrolyzate; nano-silicon dioxide and anhydrous ethanol were mixed at a mass ratio of 1:30, 10 times the mass of nano-silicon dioxide was added to the silane hydrolyzate, and the mixture was stirred at 60°C and 500 r / min for 2 h, filtered, washed with anhydrous ethanol for 5 times, and heated under vacuum at 80 ℃ and dried for 8h to obtain pre-modified nano-silica; pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine were added into a reaction kettle at a mass ratio of 1:0.6:0.5, stirred at 180℃ and 600r / min for 3h, cooled to 80℃, stirred for 1h, washed with anhydrous ethanol and deionized water for 5 times respectively, and dried at 60℃ for 7h under vacuum conditions to obtain modified nano-silica;

[0040] (3) Weigh 40 parts by mass of modified ethylene-vinyl acetate copolymer, 20 parts by mass of styrene-butadiene block copolymer, 2 parts by mass of modified nano-silicon dioxide, and 1.5 parts by mass of zinc stearate, mix them evenly, place them in a twin-screw extruder for mixing and granulation, set the temperature of the twin-screw extruder to 180° C., and the screw speed to 100 r / min to obtain a mixed masterbatch; mix the mixed masterbatch, phytic acid, and di-tert-butyl peroxide isopropyl benzene in a mass ratio of 1:0.08:0.04, place them in an internal mixer, and heat at 160 ℃, 500r / min stirring conditions for 10min, then placed in an open mill, thinned 6 times at 160℃, placed on a flat vulcanizer to be pressed into a plate, the temperature of the flat vulcanizer was set to 150℃, the pressure was 16MPa, the time was 8min, then placed in a high-pressure foaming kettle, nitrogen was used as a foaming agent for supercritical foaming, the pressure of the high-pressure foaming kettle was set to 28MPa, the temperature was set to 185℃, the pressure was released after 1h, the pressure release time was 25s, and cooled to room temperature to obtain a bio-based foaming material.

[0041] Comparative Example 1

[0042] The preparation method of the bio-based foaming material of Comparative Example 1 is different from that of Example 2 in that step (1) is not performed, and step (3) is modified as follows: 35 parts of ethylene-vinyl acetate copolymer, 15 parts of styrene-butadiene block copolymer, 1.5 parts of modified nano-silicon dioxide, and 1.25 parts of zinc stearate are weighed and mixed uniformly, and placed in a twin-screw extruder for mixing and granulation, and the temperature of the twin-screw extruder is set to 175° C. and the screw speed is 95 r / min to obtain a mixed masterbatch; the mixed masterbatch, phytic acid, and di-tert-butyl peroxide isopropylbenzene are mixed in a mass ratio of 1:0.0 7:0.035, placed in an internal mixer, mixed for 15 minutes at 155°C and 400r / min stirring conditions, then placed in an open mill, thinned 7 times at 155°C, placed on a flat vulcanizer to press into a plate, set the temperature of the flat vulcanizer to 145°C, the pressure to 15MPa, the time to 9min, then placed in a high-pressure foaming kettle, using nitrogen as a foaming agent for supercritical foaming, setting the pressure of the high-pressure foaming kettle to 26MPa, the temperature to 180°C, depressurizing after 1.5h, the depressurization time to 20s, cooled to room temperature, and obtained a bio-based foaming material. The remaining steps are the same as in Example 2.

[0043] Comparative Example 2

[0044] The preparation method of the bio-based foaming material of Comparative Example 2 is different from that of Example 2 in that step (2) is not performed, and step (3) is modified as follows: 35 parts of modified ethylene-vinyl acetate copolymer, 15 parts of styrene-butadiene block copolymer, 1.5 parts of nano-silicon dioxide, and 1.25 parts of zinc stearate are weighed and mixed uniformly, placed in a twin-screw extruder for mixing and granulation, and the temperature of the twin-screw extruder is set to 175° C. and the screw speed is 95 r / min to obtain a mixed masterbatch; the mixed masterbatch, phytic acid, and di-tert-butyl peroxide isopropylbenzene are mixed in a mass ratio of 1:0.0 7:0.035, placed in an internal mixer, mixed for 15 minutes at 155°C and 400r / min stirring conditions, then placed in an open mill, thinned 7 times at 155°C, placed on a flat vulcanizer to press into a plate, set the temperature of the flat vulcanizer to 145°C, the pressure to 15MPa, the time to 9min, then placed in a high-pressure foaming kettle, using nitrogen as a foaming agent for supercritical foaming, setting the pressure of the high-pressure foaming kettle to 26MPa, the temperature to 180°C, depressurizing after 1.5h, the depressurization time to 20s, cooled to room temperature, and obtained a bio-based foaming material. The remaining steps are the same as in Example 2.

[0045] Comparative Example 3

[0046] The preparation method of the bio-based foaming material of Comparative Example 3 is different from that of Example 2 only in step (3). Step (3) is modified as follows: 35 parts of modified ethylene-vinyl acetate copolymer, 15 parts of styrene-butadiene block copolymer, 1.5 parts of modified nano-silicon dioxide, and 1.25 parts of zinc stearate are weighed and mixed uniformly, and placed in a twin-screw extruder for mixing and granulation. The temperature of the twin-screw extruder is set to 175° C. and the screw speed is set to 95 r / min to obtain a mixed masterbatch; the mixed masterbatch and di-tert-butyl peroxide isopropylbenzene are mixed in a mass ratio of 1:0 .035, placed in an internal mixer, mixed for 15 minutes at 155°C and 400r / min stirring conditions, then placed in an open mixer, thinned 7 times at 155°C, placed on a flat vulcanizer to press into a plate, set the temperature of the flat vulcanizer to 145°C, the pressure to 15MPa, the time to 9min, then placed in a high-pressure foaming kettle, using nitrogen as a foaming agent for supercritical foaming, setting the pressure of the high-pressure foaming kettle to 26MPa, the temperature to 180°C, release the pressure after 1.5h, the pressure release time is 20s, and cooled to room temperature to obtain a bio-based foaming material. The remaining steps are the same as in Example 2.

[0047] Test Example 1

[0048] Flame retardant performance test

[0049] Test method: The limiting oxygen index of the examples and comparative examples was tested according to GB / T 2406.1. The results are shown in Table 1.

[0050] Table 1

[0051] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 30.79 Comparative Example 1 30.18 Example 2 31.25 Comparative Example 2 26.73 Example 3 30.61 Comparative Example 3 24.59

[0052] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the bio-based foaming material prepared by the present invention has good flame retardant properties.

[0053] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that pre-modified nano-silica is prepared by reacting nano-silica and 3-aminopropyltriethoxysilane, amino groups are introduced into the pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are polymerized and grown on the pre-modified nano-silica to prepare modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are thermally polycondensed by deamination of ammonia at high temperature, and a triazine structure is introduced into the modified nano-silica, and the triazine structure can generate non-flammable nitrogen-containing gas, absorb heat, dilute oxygen concentration, and improve the flame retardant properties of the bio-based foaming material.

[0054] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that the modified ethylene-vinyl acetate copolymer, styrene-butadiene block copolymer, modified nano-silica and phytic acid are mixed and granulated, and supercritically foamed to obtain the bio-based foaming material; phytic acid is an organic phosphorus compound extracted from plant seeds, containing a large amount of phosphorus element, and the introduction of phytic acid can further improve the flame retardant properties of the bio-based foaming material.

[0055] Test Example 2

[0056] Antimicrobial performance testing

[0057] Test method: Cut the examples and comparative examples into 1cmx1cm samples, wash them with ethanol and set aside; activate the Escherichia coli strains and prepare a bacterial suspension with a concentration of 2x104cfu / ml, then put the cut samples into the bacterial suspension, fix the conical flask containing the bacterial suspension and the samples on an oscillating shaker, and shake at a speed of 300r / min for 2min at a temperature of 20°C. Take 1.0ml of the bacterial suspension and dilute it to 100 times, absorb 1.0ml of the sample solution after shaking, inoculate it on the agar base, and culture it at 37°C for 48h under natural light. Count the colonies according to the method in GB15979-2003. Calculate the antibacterial rate according to the following formula: Antibacterial rate = (average colony count before sample shaking - average colony count after sample shaking) / average colony count before sample shaking x 100%. The results are shown in Table 2.

[0058] Table 2

[0059] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.73 Comparative Example 1 99.64 Example 2 99.83 Comparative Example 2 71.12 Example 3 99.68 Comparative Example 3 99.58

[0060] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the bio-based foaming material prepared by the present invention has good antibacterial properties.

[0061] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that pre-modified nano-silica is prepared by reacting nano-silica and 3-aminopropyltriethoxysilane, an amino group is introduced into the pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are polymerized and grown on the pre-modified nano-silica to prepare modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are thermally polycondensed by deamination of ammonia at high temperature, and a guanidine salt structure is introduced into the modified nano-silica, and the introduction of the guanidine salt structure can give the bio-based foaming material excellent antibacterial properties.

[0062] Test Example 3

[0063] Anti-aging performance test

[0064] Test method: According to GB / T 6344, the embodiments and comparative examples were prepared into standard specimens, and the tensile strength of the standard specimens was tested. The standard specimens were irradiated with a xenon arc lamp for 72 hours, and the tensile strength of the standard specimens after ultraviolet aging treatment was tested by the same method. The change rate of the tensile strength of the embodiments and comparative examples before and after ultraviolet aging treatment was calculated, tensile strength change rate = (tensile strength of standard specimens - tensile strength of standard specimens after ultraviolet aging treatment) / tensile strength of standard specimens × 100%. The results are shown in Table 3.

[0065] Table 3

[0066]

[0067] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the bio-based foaming material prepared by the present invention has good anti-aging performance.

[0068] By comparison, the change rate of tensile strength of Examples 1 to 3 is smaller than that of Comparative Example 1, indicating that the spiropyran ultraviolet absorber is prepared by reacting (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde, and a carbon-carbon double bond and a hydroxymethyl group are introduced into the spiropyran ultraviolet absorber; the spiropyran ultraviolet absorber is a spiro carbon atom connected by an SP3 hybridization, and two aromatic rings are mutually orthogonal, and no molecular structural conjugation is generated to form a closed ring body. After being excited by ultraviolet light, the spiro oxygen bond in the molecule undergoes heterolytic cleavage and the electronic configuration undergoes isomerization or rearrangement to become a coplanar open ring body of two ring systems, and the entire molecule forms a large conjugated plane. The open ring body can be re-closed to form a closed ring body under visible light irradiation or heating, thereby giving the bio-based foaming material excellent anti-aging properties.

[0069] Test Example 4

[0070] Wear resistance test

[0071] Test method: The examples and comparative examples were cut into cylindrical specimens with a diameter of 16 mm and a height of 10 mm. The volume wear of the specimens was measured using a DIN roller abrasion tester according to the international standard ISO 4649-2010. The roller had a diameter of 150 mm and a length of 500 mm and rotated clockwise at a speed of 40 r / mm. Three parallel tests were performed on each specimen and the average value was taken. The results are shown in Table 4.

[0072] Table 4

[0073]

[0074]

[0075] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 4, it can be found that the bio-based foaming material prepared by the present invention has good wear resistance.

[0076] By comparison, the volume abrasion of Examples 1 to 3 is less than that of Comparative Example 1, indicating that the spiropyran UV absorber is prepared by reacting (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde, and carbon-carbon double bonds and hydroxymethyl groups are introduced into the spiropyran UV absorber; the carbon-carbon double bonds in the spiropyran UV absorber are melt-grafted onto the side chains of ethylene-vinyl acetate copolymers to prepare modified ethylene-vinyl acetate copolymers, and hydroxymethyl groups are introduced into the side chains of the modified ethylene-vinyl acetate copolymers. The hydroxymethyl groups can be dehydrated with the phosphate groups on phytic acid under high temperature and high pressure to form a cross-linked network, thereby inhibiting the relative slip of the molecular chains, stabilizing the final pore structure, and improving the mechanical properties of the bio-based foaming material. The molecular chains are not easily torn by external shear forces, thereby enhancing the wear resistance.

[0077] By comparison, the volume loss of Examples 1 to 3 is less than that of Comparative Example 2, indicating that pre-modified nano-silica is prepared by reacting nano-silica and 3-aminopropyltriethoxysilane, an amino group is introduced into the pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are polymerized and grown on the pre-modified nano-silica to prepare modified nano-silica, 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine are thermally condensed at high temperature to remove ammonia, an amino group is introduced into the modified nano-silica, and the amino group on the modified nano-silica is polymerized and grown. The base can also be dehydrated with the phosphate group on phytic acid under high temperature and high pressure to form a cross-linked network, inhibiting the relative slip of the molecular chains, making the final pore structure stable, and at the same time improving the mechanical properties of the bio-based foaming material. The molecular chains are not easily torn by external shear forces, thereby enhancing the wear resistance. Nano-silica has a high specific surface area and excellent mechanical properties, which can improve the strength and hardness of the matrix resin. The nano-silica can be modified to increase the compatibility of the nano-silica with the matrix resin, reduce the agglomeration of the nano-silica, and make the nano-silica evenly dispersed in the matrix resin, so as to give full play to the reinforcing effect of the nano-silica and further improve the wear resistance of the bio-based foaming material.

[0078] By comparison, the volume wear of Examples 1 to 3 is less than that of Comparative Example 3, indicating that the modified ethylene-vinyl acetate copolymer, styrene-butadiene block copolymer, modified nano-silica and phytic acid are mixed and granulated, and supercritical foaming is performed to obtain the bio-based foaming material; phytic acid is an organic phosphorus compound extracted from plant seeds, containing a large number of phosphate groups. The phosphate groups in phytic acid can be dehydrated with the hydroxymethyl groups on the modified ethylene-vinyl acetate copolymer and the amino groups on the modified nano-silica under high temperature and high pressure to form a cross-linked network, thereby inhibiting the relative slip of the molecular chains, stabilizing the final pore structure, and improving the mechanical properties of the bio-based foaming material. The molecular chains are not easily torn by external shear forces, thereby enhancing the wear resistance.

[0079] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A bio-based foaming material, characterized in that: The bio-based foaming material is prepared by reacting a spiropyran ultraviolet absorber and an ethylene-vinyl acetate copolymer to obtain a modified ethylene-vinyl acetate copolymer; polymerizing and growing 1,3-diaminoguanidine hydrochloride and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine on pre-modified nano-silica to obtain modified nano-silica; and mixing and granulating the modified ethylene-vinyl acetate copolymer, a styrene-butadiene block copolymer, the modified nano-silica and phytic acid, and performing supercritical foaming to obtain the bio-based foaming material. The spiropyran ultraviolet absorber is prepared by reacting (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde; The pre-modified nano silicon dioxide is prepared by reacting nano silicon dioxide and 3-aminopropyltriethoxysilane.

2. A method for preparing a bio-based foaming material, characterized in that: The preparation method of the bio-based foaming material comprises the following preparation steps: (1) mixing spiropyran ultraviolet absorber, diisopropyl peroxide and acetone in a mass ratio of 1:(0.1-0.12):(3-4), stirring at 10-30°C and 300-500 r / min for 3-5 min, adding ethylene-vinyl acetate copolymer in an amount of 45-55 times the mass of the spiropyran ultraviolet absorber, continuing stirring for 10-12 min, standing for 11-13 h, placing in a plasticizer for melting and plasticizing, setting the plasticizing temperature to 170-180°C, the screw speed to 40-50 r / min, the plasticizing time to 10-12 min, and drying at 50-60°C under vacuum conditions for 3-4 h to obtain a modified ethylene-vinyl acetate copolymer; (2) adding pre-modified nano-silica, 1,3-diaminoguanidine hydrochloride, and 2,4-diamino-6-[3-(trifluoromethyl)phenyl]-1,3,5-triazine in a mass ratio of 1:(0.4-0.6):(0.3-0.5) into a reaction kettle, stirring at 160-180° C. and 400-600 r / min for 3-4 h, cooling to 70-80° C., stirring for 1-2 h, washing with anhydrous ethanol and deionized water for 3-5 times each, and drying at 50-60° C. for 7-8 h under vacuum conditions to obtain modified nano-silica; (3) Weigh 30-40 parts by mass of modified ethylene-vinyl acetate copolymer, 10-20 parts by mass of styrene-butadiene block copolymer, 1-2 parts by mass of modified nano-silicon dioxide, and 1-1.5 parts by mass of zinc stearate, mix them evenly, place them in a twin-screw extruder for mixing and granulation, and prepare a mixed masterbatch; mix the mixed masterbatch, phytic acid, and di-tert-butyl peroxide isopropyl benzene in a mass ratio of 1:(0.06-0.08):(0.03-0.04), place them in an internal mixer, and heat at 150-1 The mixture was mixed at 60°C and 300-500r / min for 10-20min, then placed in an open mill, thinned 6-8 times at 150-160°C, pressed into a plate on a flat vulcanizer, and then placed in a high-pressure foaming kettle, using nitrogen as a foaming agent for supercritical foaming, setting the pressure of the high-pressure foaming kettle to 24-28MPa and the temperature to 175-185°C, releasing the pressure after 1-2h, and the pressure release time to 15-25s. The mixture was cooled to room temperature to obtain a bio-based foaming material.

3. The method for preparing a bio-based foaming material according to claim 2, characterized in that: The preparation method of the spiropyran ultraviolet absorber in step (1) is as follows: (1,3,3-trimethyl-2-methylene-2,3-dihydro-1H-indol-6-yl)-methanol and 3-allyl salicylaldehyde are added in a molar ratio of 1:1 to methanol with a mass of 14 to 16 times that of 3-allyl salicylaldehyde; in a nitrogen atmosphere, the mixture is stirred and refluxed at 65 to 75° C. and 300 to 500 r / min for 2 to 3 hours; and in a vacuum condition, the mixture is dried at 50 to 60° C. for 7 to 9 hours to obtain the spiropyran ultraviolet absorber.

4. The method for preparing a bio-based foaming material according to claim 2, characterized in that: The model of the ethylene-vinyl acetate copolymer in step (1) is Y2045 18-3.

5. The method for preparing a bio-based foaming material according to claim 2, characterized in that: The preparation method of the pre-modified nano-silica in step (2) is as follows: nano-silica and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(20-30), silane hydrolyzate is added in an amount of 8-10 times the mass of the nano-silica, the mixture is stirred at 50-60°C and 300-500 r / min for 2-3 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 70-80°C under vacuum conditions for 8-10 hours to obtain the pre-modified nano-silica.

6. The method for preparing a bio-based foaming material according to claim 5, characterized in that: The preparation method of the silane hydrolyzate is as follows: 3-aminopropyltriethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(40-50), the pH value is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the silane hydrolyzate is prepared by stirring at 10-30° C. and 300-500 r / min for 50-60 min.

7. The method for preparing a bio-based foaming material according to claim 2, characterized in that: The model of the styrene-butadiene block copolymer in step (3) is: HJ15A.

8. The method for preparing a bio-based foaming material according to claim 2, characterized in that: The process parameters of the twin-screw extruder in step (3) are as follows: the temperature of the twin-screw extruder is set to 170-180° C., and the screw speed is set to 90-100 r / min.

9. The method for preparing a bio-based foaming material according to claim 2, characterized in that: The process parameters of the plate vulcanizer in step (3) are as follows: the temperature of the plate vulcanizer is set to 140-150° C., the pressure is set to 14-16 MPa, and the time is set to 8-10 min.

Citation Information

Patent Citations

  • Modified EVA, preparation method thereof and wide-temperature-range high-performance EVA composite foaming material

    CN113845716A

  • Anti-PID type EVA adhesive film for photovoltaic module and preparation method of anti-PID type EVA adhesive film

    CN116396688A

  • Light-operated force-electric material and preparation method and application thereof

    CN117430880A

  • Photochromic fabric

    CN117488546A

  • Shoe material composition based on biomass raw materials and foaming shoe material

    CN117700866A